Global Rotavirus and Pneumococcal Conjugate Vaccine Introductions and the Association With Country Disease Surveillance, 2006–2018. (1st September 2021) - Peck, Megan E; Hampton, Lee M; Antoni, Sebastian; Ogbuanu, Ike; Serhan, Fatima; Nakamura, Tomoka; Walldorf, Jenny A; Cohen, Adam L
Abstract: Background: To inform the introduction of pneumococcal conjugate vaccine (PCV) and rotavirus vaccine, the World Health Organization (WHO) established the Global Invasive Bacterial Vaccine-Preventable Disease Surveillance Network (GISN) and the Global Rotavirus Surveillance Network (GRSN) in 2008. We investigated whether participation in these networks or other surveillance was associated with vaccine introduction. Methods: Between 2006 and 2018, among all WHO member states, we used multivariable models adjusting for economic status to assess (1) the association between surveillance for pneumococcal disease or rotavirus disease, including participation in GISN or GRSN and the introduction of the PCV or the rotavirus vaccine, respectively, and (2) the association between the rotavirus disease burden and the rotavirus vaccine introduction among 56 countries participating in GRSN from 2008 to 2018. Results: Countries that participated in or conducted surveillance for invasive pneumococcal disease or rotavirus disease were 3.5 (95% confidence interval [CI], 1.7–7.1) and 4.2 (95% CI, 2.1–8.6) times more likely to introduce PCV or rotavirus respectively, compared to those without surveillance. Among countries participating in GRSN, there was insufficient evidence to demonstrate an association between countries with higher rotavirus positivity and vaccine introduction. Conclusions: Surveillance should be incorporated into advocacy strategies to encourage the introduction of vaccines, with countries benefiting from data from, support for, and coordination of international disease surveillance networks.